2022
DOI: 10.1091/mbc.e21-08-0418
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional response to oxidative stress is independent of stress-granule formation

Abstract: Cells respond to stress with translational arrest, robust transcriptional changes, and transcription-independent formation of mRNP assemblies termed stress granules (SGs). Despite considerable interest in the role of SGs in oxidative, unfolded-protein and viral stress responses, whether and how SGs contribute to stress-induced transcription has not been rigorously examined. To address this, we characterized transcriptional changes in Drosophila S2 cells induced by acute oxidative-stress and assessed how these … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 133 publications
0
3
0
Order By: Relevance
“…However, translation initiation of the RNAs stored in stress granules has been shown not to be required for growth, as translation can resume before stress granule clearance is complete ( Loschi et al., 2009 ; Walters et al., 2015 ). Furthermore, a recent study suggests that the mRNAs that are upregulated upon oxidative stress are vastly excluded from stress granules ( Singh et al., 2021 ), strengthening the notion that stress granules might not be needed to protect RNA from degradation, but simply store them. Last, contrary to the finding that stress granules do not contain fully assembled ribosomes (only 40S) ( Kedersha et al., 1999 ; Anderson and Kedersha, 2002 ), single-molecule imaging has revealed that the translation machinery can be activated in stress granules ( Mateju et al., 2020 ).…”
Section: Discussionmentioning
confidence: 91%
“…However, translation initiation of the RNAs stored in stress granules has been shown not to be required for growth, as translation can resume before stress granule clearance is complete ( Loschi et al., 2009 ; Walters et al., 2015 ). Furthermore, a recent study suggests that the mRNAs that are upregulated upon oxidative stress are vastly excluded from stress granules ( Singh et al., 2021 ), strengthening the notion that stress granules might not be needed to protect RNA from degradation, but simply store them. Last, contrary to the finding that stress granules do not contain fully assembled ribosomes (only 40S) ( Kedersha et al., 1999 ; Anderson and Kedersha, 2002 ), single-molecule imaging has revealed that the translation machinery can be activated in stress granules ( Mateju et al., 2020 ).…”
Section: Discussionmentioning
confidence: 91%
“…Amongst them is Rootletin, which is known to play a role in behavioural response in Drosophila [ 64 ] and was previously linked to resistance as a key hub in response to insecticide exposure [ 45 ], whilst Grau has been linked to pyrethroid resistance in Aedes populations [ 65 ]. Other transcription factors enriched in insecticide resistance-related terms that are consistent with known roles in Drosophila includes Cabut, which has been shown to regulate stress response [ 66 ], E(spl)m3-HLH which is linked with stress granules [ 67 ], Grh that is involved in cuticular repair [ 68 ], Exex is involved in neuronal function [ 69 ], Onecut with synapse organisation [ 70 ] and Tfam is a mitochondrial transcription factor, with a role in oxidative stress response [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic analysis was shown that perturbations of at least 128 genes cause nucleolar enlargement with subsequent formation of stress granules, an increase in the number of Cajal bodies, and splicing speckles in mammalian cells [ 214 ]. In addition, this work established a correlation between an increase in the nucleolus and a decrease in P-bodies, wherein no relationship was found between changes in gene expression and the formation of cytoplasmic stress granules [ 215 ].…”
Section: Discussionmentioning
confidence: 99%